Proof: Reduce Addition

Let's prove the following theorem:

if the following are true:
  • ((a + a) + a) + a = 360
  • not (4 = 0)

then a = 90

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 ((a + a) + a) + a = 360
2 not (4 = 0)
Proof Table
# Claim Reason
1 ((a + a) + a) + a = a4 ((a + a) + a) + a = a4
2 a4 = 360 if ((a + a) + a) + a = 360 and ((a + a) + a) + a = a4, then a4 = 360
3 a = 360 / 4 if not (4 = 0) and a4 = 360, then a = 360 / 4
4 360 / 4 = 90 360 / 4 = 90
5 a = 90 if 360 / 4 = 90 and a = 360 / 4, then a = 90

Comments

Please log in to add comments